The "Local" (meat?) hunter? Backbone or bain.... ...of the game wildlife rancher...? - Palos, Stephen, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Making the most of the "bread & milk shopper" requires appreciating their importance, providing for their needs, keeping them "low maintenance", maximising the "basket" and ensuring they select animals which meet management objectives of the ranch. This presentation aims to explore the value of the most basic "customer" of the Wildlife Rancher. Coming from a "Greek South African" up-bringing the presentation will be in "Café Speak" and aims to take a light hearted and amusing view of an incredibly important aspect of the business, encouraging fresh thoughts on the subject and perhaps some specific initiatives by representative organisations to further develop the relationship between the rancher and the meat hunter. Studies in South Africa indicate that the local meat hunter brings in excess of 70% of the revenue to the Wildlife Rancher's gate. But average take per animal is far lower than what international trophy hunters bring. Different too is the expected hunting method or style, and the expectations in relation to services and accommodation. Extreme contrast exists from the most ethical, humble traditionalist (with a tiny "bag" in mind) to big groups of well heeled "corporate hunters" who aim to "whack em & stack em" in between raucous partying, and everything possible in between; each bringing pros & cons!
The local (meat?) hunter? Backbone or bain.... ...of the game wildlife rancher...?
The local meat hunter: backbone or bain of the game rancher's business
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.